Hotspots and trends in frozen soils research in 2010–2019. (3rd April 2023) - Liu, Wenhao; Li, Ren; Shi, Xiaoqian; Wu, Tonghua; Wu, Xiao Dong
Abstract: In the context of climate change, research on frozen soils has attracted much attention in recent years, and numerous research papers have been published on these topics in the last decade. However, the present status and developmental trends in frozen soils research have not been reported systematically. Herein, a bibliometric analysis was conducted using 7, 108 research papers on frozen soils published between 2010 and 2019. The results indicate that: (a) although the number of articles published increased from 432 in 2010 to 1, 066 in 2019, the average number of citations per paper reached a maximum of 5.40 in 2014, and subsequently decreased to 2.99 in 2019; (b) China, the USA, and Canada ranked first to third in terms of total papers; (c) the most popular author keywords were boreal, tundra, Landsat, lakes, decomposition, dissolved organic carbon, permafrost thaw, and carbon cycle; and (d) the five most popular research topics in 2010–2019 were the characteristics and factors influencing frozen soils, the Arctic carbon cycle under the background of its complex environment, permafrost changes on the Qinghai–Tibet Plateau in the context of climate change, ancient frozen soils in various historical periods, and frozen soils in the Arctic.